My family and other animus - Jeffrey, James, 1972- (Melbourne University Press, 2018)
An ode to family life in all its glorious mess and chaos. For the young James Jeffrey, the day his parents split was like the splitting of the atom. Life took on a seismic instability filled with madness and strain and vendetta and daftness and acts of love, both beautiful and misguided. Yet, what could have been a calamitous upbringing turned instead into an education. For better or worse, his family handed out lessons that would guide him through life, into marriage, and eventually parenthood. My Family and Other Animus is an ode to his family.